Hold me tight seven conversations for a lifetime of love - Johnson, Susan M. (New York : Little, Brown & Co., 2008)
Introduces the author's Emotionally Focused Therapy technique, explaining how to assist couples by treating their relationship as a love-based, attachment bond that can be healed through a reestablishment of safe emotional connections.
A new light on love. A revolutionary new view ; Where did our love go? : losing connection -- Emotional responsiveness : the key to a lifetime of love -- Seven transforming conversations. Recognizing the demon dialogues ; finding the raw spots ; Revisiting a rocky moment ; Hold me tight : engaging and connecting ; forgiving injuries ; bonding through sex and touch ; Keeping your love alive -- The power of hold me tight. Healing traumatic wounds : the power of love ; Ultimate connection : love as the final frontier.
Includes bibliographical references (pages 281-289) and index.
105991
Keywords: Love; Intimacy (Psychology); Interpersonal communication; Communication in marriage; Man-woman relationships; Communication in marriage; Interpersonal communication